The role of systemic hypermobility and condylar hypermobillity in temporomandibular joint dysfunction syndrome. - Kavuncu, V; Sabin, S; Kamanli, A; Karan, A; Aksoy, C (Wiley, 2002)
[Abstract Not Available]
66th Annual Scientific Meeting of the American-College-of-Rheumatology/37th Annual Scientific Meeting of the Association-of-Rheumatology-Health-Professionals -- OCT 24-29, 2002 -- NEW ORLEANS, LA